2006
DOI: 10.1108/02635570610640988
|View full text |Cite
|
Sign up to set email alerts
|

Understanding management data systems for enterprise performance management

Abstract: PurposeManaging enterprise performance is an important, yet a difficult process due to its complexity. The process involves monitoring the strategic focus of an enterprise, whose performance is measured from the analysis of data generated from a wide range of interrelated business activities performed at different levels within the enterprise. This study aims to investigate management data systems technologies in terms of how they are used and the issues that are related to their effective management within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 17 publications
0
41
0
1
Order By: Relevance
“…Few (2006) state the dashboard as "a visual display of the most important information needed to achieve one or more objectives; consolidated and arranged on a single screen so the information can be monitored at a glance" (Few, 2006). Bose (2006) describe dashboard as "a software application that provides a single-screen display of relevant and critical business metrics and analytics to enable faster and more effective decision making".…”
Section: Conceptualization Of Dashboardmentioning
confidence: 99%
“…Few (2006) state the dashboard as "a visual display of the most important information needed to achieve one or more objectives; consolidated and arranged on a single screen so the information can be monitored at a glance" (Few, 2006). Bose (2006) describe dashboard as "a software application that provides a single-screen display of relevant and critical business metrics and analytics to enable faster and more effective decision making".…”
Section: Conceptualization Of Dashboardmentioning
confidence: 99%
“…The BSC framework also supports learning and knowledge creation in its learning and growth dimension (Kaplan & Norton, 1996). Companies have also started using IT systems to learn from data and support decision making (Bose, 2006). Facts like these demonstrate that PM has shifted its focus from control to learning, especially because of the emergence of concepts such as KM and systems thinking (Brudan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…'The challenge is the interpretation of multiproduct, multi-functional information. Bose (2006) identified that the key issue is to develop key performance indicators (KPIs) that provide a holistic and balanced view of the business. 'One potential approach is to think of individual KPIs not just as a singular metric, but as a balanced metric that incorporates several alternative dimensions ' (p.56).…”
Section: Issues Identified In Designing Performance Metrics For Markementioning
confidence: 99%